2023
DOI: 10.1021/acs.jpclett.3c02651
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally Resolved Absorption, Fluorescence, and Preresonance Raman Spectroscopy of Isolated Pyronin Y Cation at 5 K

Sreekanta Debnath,
Alexander Schäfer,
Shun Ito
et al.

Abstract: Exploring how charge-changing affects the photoluminescence of small organic dyes presents challenges. Here, helium tagging photodissociation (PD) action spectroscopy in the gas phase and dispersed laser-induced fluorescence (DF) spectroscopy in the solid Ne matrix are used to compare the intrinsic photophysical properties of pyronin Y cation [PY] + and its one electron-reduced neutral radical [PY] • at 5 K. Whereas the cation shows efficient visible photoluminescence, no emission from the neutral, in line wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 49 publications
3
3
0
Order By: Relevance
“…the fluorescence excitation spectrum (λ max = 445 nm). This is as expected owing to the lower thermal energy of the ions in the He-TAG experiment (and therefore reduced population of vibrationally excited electronic ground state species). Interestingly though, while the two distinctive sets of absorption features in our PD spectrum are not resolved in their fluorescence excitation spectrum, Dobbie et al recorded a DF spectrum showing two partially resolved emission bands (discussed later) …”
supporting
confidence: 71%
See 4 more Smart Citations
“…the fluorescence excitation spectrum (λ max = 445 nm). This is as expected owing to the lower thermal energy of the ions in the He-TAG experiment (and therefore reduced population of vibrationally excited electronic ground state species). Interestingly though, while the two distinctive sets of absorption features in our PD spectrum are not resolved in their fluorescence excitation spectrum, Dobbie et al recorded a DF spectrum showing two partially resolved emission bands (discussed later) …”
supporting
confidence: 71%
“…As reported by us for other fluorophores, ,,, we have observed that both [ACF] + and [mpf] + can also undergo some charge changing during soft-landing deposition into neon, resulting in strongly fluorescent neutrals which emit significantly to the red of their charged precursors when excited in the UV. We will report details in a future study .…”
supporting
confidence: 71%
See 3 more Smart Citations